PEDATREN: MANAJEMEN PESANTREN BERBASIS PAPERLESS OFFICE - Amin, Moh. Badruddin; Adhimy, Syafiqiyah (re-JIEM (Research Journal of Islamic Education Management), 2020)
This article aims to understand pedatren holistically as a technology-based paperlessoffice boarding school management solution. This article uses qualitative research with the types of case studies conducted at Nurul Jadid Islamic Boarding School, Paiton, Probolinggo. Nurul Jadid Islamic Boarding School is one of the pesantren in East Java which has been established for 69 years. This is an indicator that the Nurul Jadid Islamic Boarding School is able to survive, be responsive and dynamic towards changing times, without abandoning religious values as a whole. Nurul Jadid Islamic Boarding School is also one of the cottages that responds well to the presence of technology. Pedatren is the solution to the pesantren management system which is starting to transform towards a paperless institution. Pedatren is designed using the node.js programming language with the jami ’wal mani’ design system.